Concept Of Criminal Liability Of Notary Law In Deed Making Based On Perjury - Ailina Rahmanita Fauzi; Iin Khaeriyatun Ni'mah; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Purpose research These are 1) To analyze the concept of criminal responsibility notary law in the deed that is based on false information. 2) To analyze the legal consequences of the deed notary Based on False Information.The method used by researchers is Empirical Juridical (socio legal research)and specification in this study were included descriptive analysis. Even the sources and types of data in this study are primary data obtained from field studies with an interview with a notary in Grobogan. And secondary data obtained from the study of literature. This study uses qualitative data analysis Based on the results of research that 1) Notaries can not be held criminal liability associated with the manufacture of the deed (partijnakten) based on false information, and can not meet the crime of counterfeiting element formulation in Article 266 paragraph (1) in conjunction with Article 55 paragraph (1) of the Criminal Code. 2) However, the notary can be held criminal liability against relaas deed or deed of officials (ambtelijke akten) if deliberate or careless notary make a fake deed to the detriment others. That made base on notary deed against false information does not in itself result in the deed null and void. The aggrieved party to the existence of the deed as it should file a civil suit to the court to cancel the deed.Keywords : Concept of Law; Criminal Responsibility; Notary; Deed; Specification False